Gestão e uso de si do egresso Técnico de Segurança do Trabalho : cenografia e ethos construidos na formação profissional e na concretude da atividade laboral - Ribeiro, Elaine (2023)
The study developed in this thesis presents as its theme the interface language and work: dialogues between Ergology and Discourse Analysis. The general objective is to describe and analyze the discursive practices expressed by Occupational Safety Technicians, graduates of Instituto Federal Catarinense, Fraiburgo Campus- Santa Catarina, in real work situation, who build scenographies from which discursive ethos emerge, as image of themselves, which mobilize knowledge and values arising from prescripts and work re-standardization. This study relies on theoretical conceptions in interface which involve: Ergology by Yves Schwartz (2006, 2010, 2011, 2013, 2014, 2016), Schwartz and Durrive (2008, 2010, 2015), Durrive (2011), Faïta (2002), Souza and Silva (2002, 2014, 2019), Nouroudine (2002, 2011) and Trinquet (2010) and theoretical assumptions of French Discourse Analysis, by Dominique Maingueneau (2008, 2013, 2015, 2018, 2019, 2020). The formulated thesis is that the discursive practices discoursed by the Occupational Safety Technicians, graduates of Instituto Federal Catarinense, Fraiburgo Campus, in Santa Catarina, build scenographies, in real work situation, which configure discursive ethos, as an image of themselves, which mobilize knowledge and values resulting from the prescripts and work re-standardization. The methodology adopted in this investigation, regarding the objectives, is characterized as exploratory; as the technical procedures, the study is classified as bibliographical, documental and field research. Concerning the approach of the problem, a qualitative research was used. The corpora selected for analysis comprise prescriptions/norms established in the Pedagogical Project of the Technical Course in Occupational Safety, at Instituto Federal Catarinense, Fraiburgo Campus - Santa Catarina - and three oral reports referring to the actual work activity, verbalized voluntarily, through semi-structured interviews, by three Instituto Federal Catarinense graduates. The results of the analysis indicate that the scenography constructed in the speeches by the protagonists of the study are constantly influenced by the daily inconsistencies that arise in the distance established between the prescribed and the actual work activity. In an attempt to control the visible and invisible dimensions that are established in this distance, the subjects reveal, in the discourse about work, dramatic uses of themselves for themselves and of themselves by others experienced by themselves, building different discursive ethos in the concrete performance of the labor activity.